BUDIDAYA IKAN NILA PILIHAN UNTUK MENGATASI KETERGANTUNGAN PENDUDUK TERHADAP SUMBER DAYA HAYATI TAMAN NASIONAL KERINCI SEBLAT DI NAGARI LIMAU GADANG LUMPO - Armen, Armen (IAIN Batusangkar, 2015)
The purpose of this research is to tilapia fish farming options to address the population's dependence on natural resources Kerinci National Park (TNKS) at Nagari Limes Tower Lumpo South Coastal District. The study involved people with the characteristics of the profession in the forest breadwinner TNKS with 40 households. In the year I conducted research information and guidance on: (1) the benefits to the ecosystem and human TNKS and the risk of making a living in TNKS; (2) create a pond breeding and rearing of tilapia; (3) the breeding and mendeder tilapia; (4) to make fish feed; (5) to collect data of economic activity conducted sample population. In II was found (1) fingerlings 25,000; (2) The rearing ponds and nursery 5 units, (3) feed production has been carried out by farmers. The findings of this study in the second year compared. Data taken form the sample frequency of visits to TNKS. The second year study lasted for 6 months. To see the similarities or differences between the mean results of economic activity used formula T-Test statistics. The results showed that the average percentage of traffic TNKS sample members for 6 months to 86%. Based on research on second year level visit to the pool group members each month TNKS 75.06%. The mean rate of decline in the frequency of visits to group members TNKS an approximately 11.06%. Decreased levels of group members visit the pool to TNKS the second year that the guide member can mengatasai tilapia fish farming population's dependence on TNKS. Thus concluded that the tilapia fish farming has made the choice to overcome the dependence on natural resources population Kerinci National Park (TNKS) at Nagari Limes Tower Lumpo South Coastal District with fairly good results,Key words: TNKS, Aquaculture, Tilapia, Natural Resources, Economic Activity